2014
DOI: 10.1007/s00477-014-0983-3
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic contaminant transport monitoring in heterogeneous sand and gravel aquifers of the United Arab Emirates

Abstract: Stochastic numerical simulations were performed to investigate the evolution of plumes from pulse sources that can result from accidental leaks. The stochastic advection-dispersion equation was solved for hydraulic conductivities typical to the heterogeneous sandy and gravel aquifers encountered in the United Arab Emirates. Dispersivities were similar to those found in field studies at sandy aquifers, such as those conducted at Borden and Cape Cod, and at the Vejen, Denmark tracer tests. Our work showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…However, recent studies reported that the annual rainfall of the country experienced a downward shift in 1999, and the average rainfall has decreased when compared to annual rainfall before the shift [9,12,36]. The country's aquifers are composed of interior heterogeneous sand aquifers, gravel aquifers in the Eastern and Western plains, and coastal and limestone aquifers [37]. The limited UAE agriculture industry is largely dependent on groundwater and the major arable land is located in the northeastern region.…”
Section: Study Areamentioning
confidence: 99%
“…However, recent studies reported that the annual rainfall of the country experienced a downward shift in 1999, and the average rainfall has decreased when compared to annual rainfall before the shift [9,12,36]. The country's aquifers are composed of interior heterogeneous sand aquifers, gravel aquifers in the Eastern and Western plains, and coastal and limestone aquifers [37]. The limited UAE agriculture industry is largely dependent on groundwater and the major arable land is located in the northeastern region.…”
Section: Study Areamentioning
confidence: 99%
“…The water table at the coastal areas of UAE is less than 1 m below the surface, and this is where the two major population centers, Abu Dhabi and Dubai, are located. Even in the interior at the city of Al Ain, close to the border with Oman, the water table is a few tens of meters below ground surface [17]. Although heterogeneous the subsurface environment is characterized by high permeability material.…”
Section: The Waste-to-energy Option For the City Of Abu Dhabimentioning
confidence: 99%